A 1D P-Wave Velocity Model of the Northern Thailand - Mungharkaew S. (2023)
The 6 initial models were tested to obtain the best 1D velocity model, called NTh1D model, to improve earthquake location in the northern part of Thailand. After testing the layer thickness of IASP91 model, the 2 km grid size and 32 km crustal thickness of the northern Thailand show the also show the minimum error. The NTh1D model shows more accurate hypocenter solution compare with original IASP91 and other models tested in this study. The station corrections were also reported to produced better earthquake locations.